A Shared Vision? Exploring the Perceptions of Principals and Teachers Regarding the Middle School Concept - Shawn A. Faulkner; Chris Cook; Ryan Alverson; Mike DiCicco (Middle Grades Review, 2023)
From decades of recommendations, middle school advocates have recommended various organizational structures and instructional practices to meet the specific educational needs of young adolescents. Several notable national studies have sought to assess and report the status of implementation of these recommended practices, though largely from the perspective of the building principal. The purpose of this study was to examine both teachers’ and principals’ perceptions concerning the middle school concept. Based on responses of over 1,600 teachers and principals from all 50 states, findings indicate support for components of the middle school concept related to curriculum and instruction as well as school culture; however, support for components related to middle school philosophy and organizational structures received the lowest levels of support from principals and teachers. While reported support for middle school students was encouraging, the waning support for the philosophical and organizational components often considered foundational to the middle school concept was concerning.
Keywords: middle schools; middle school concept